Modelling under risk and uncertainty : an introduction to statistical, phenomenological, and computational methods - Rocquigny, Etienne de. (Hoboken, NJ : Wiley, 2012)
'This volume addresses a concern of very high relevance and growing interest for large industries or environmentalists: risk and uncertainty in complex systems. It gives new insight on the peculiar mathematical challenges generated by recent industrial safety or environmental control analysis, focusing on implementing decision theory choices related to risk and uncertainty analysis through statistical estimation and computation, in the presence of physical modeling and risk analysis. The result will lead statisticians and associated professionals to formulate and solve new challenges at the frontier between statistical modeling, physics, scientific computing, and risk analysis'--
'This book aims at giving a new insight on the peculiar mathematical challenges generated by recent industrial safety or environmental control analysis'--
Includes bibliographical references and index.
Keywords: Industrial management -- Mathematical models; Uncertainty -- Mathematical models; Risk management -- Mathematical models; MATHEMATICS / Probability & Statistics / General